POI04 Transverse myelitis—a single centre review. Issue 11 (22nd October 2010) - Panicker, J; Jones, A; Jacob, A
Abstract : Introduction: Inflammatory demyelinating transverse myelitis can be the first presentation of multiple sclerosis or neuromyelitis optica or remain an isolated event—idiopathic acute transverse myelitis (ATM). Data on relative proportions of these or on ATM are sparse from the UK. Methods: A case note review of all cases recorded as "myelitis" from 2003 to 2008 in electronic medical records was done and final diagnoses verified. A detailed review of cases whose diagnosis remained as ATM was performed. Results: Of the 324 notes reviewed 222 (68%) had noninflammatory myelopathies; 102 (31%) had inflammatory myelitis. TM was the first presentation of MS in 53%, NMO in 15%, and ATM in 24%. Fifteen (66%) were women. Eight patients (32%) had a preceding trigger and the first symptom was sensory in 18. The median Hughes score was 3 at nadir. At last review (median of 12 months). This had improved to 2 but medications were needed in 72% for residual symptoms. Conclusions: A quarter of patients with an initial presentation of inflammatory myelitis have ATM and continue to have moderate disability on follow-up. Research into effective treatments and implementation of current best practice are needed to optimise outcomes.